The Effectiveness of Communication on Generasi Pesona Indonesia’s Instagram in Fulfilling Tourism Informationn Needs - Achmad Syah Galang Ramadhan; Sandrina Humaira (Universitas Muhammadiyah Sidoarjo, 2023)
The rise of social media platforms has transformed the way individuals access information, with Instagram emerging as a potent medium due to its visual appeal and engaging features. This research, titled